A Cross-Cultural Study of University Students’ e-Learning Adoption - Stela Jorgji; Ainash Davletova; Sandugash Assylbekova; Elena Susimenko; Elena Kulikova; Mikhail Kosov; Elena Vlasova; Lyudmila Shcherbatykh; Kundharu Saddhono; Olesya Dudnik (Emerging Science Journal, 2024)
This study aims to investigate the differences in e-learning adoption among university students in Indonesia, Albania, Russia, and Kazakhstan and examine the role of cultural dimensions in explaining these differences. This research draws upon Hofstede’s Cultural Dimensions Theory to explore the impact of culture on e-learning adoption in diverse global contexts. A cross-sectional survey was conducted with a sample of university students from the four countries, and the data were analyzed using structural equation modeling (SEM) and multi-group analysis (MGA) techniques. The findings reveal significant differences in e-learning adoption among the four countries, with learner engagement, learning satisfaction, and technology accessibility exhibiting varying levels of influence on e-learning adoption. The multi-group analysis indicates that cultural dimensions partially explain these differences, highlighting the importance of considering cultural factors when examining e-learning adoption in diverse settings. This study fills a gap in cross-cultural e-learning research, offering key insights into factors shaping students’ adoption of online platforms worldwide. The findings emphasize the importance of cultural considerations for educators, policymakers, and e-learning developers in global higher education. This study contributes to the theoretical understanding of the complex interplay between culture and e-learning adoption by demonstrating the explanatory power of cultural dimensions.